The safety of maternal immunization - Regan, Annette (2016)
Maternal vaccination offers the opportunity to protect pregnant women and their infants against potentially serious disease. As both pregnant women and their newborns are vulnerable to severe illness, the potential public health impact of mass maternal vaccination programs is remarkable. Several high-income countries recommend seasonal influenza and acellular pertussis vaccines, and many developing countries recommend immunization against tetanus during pregnancy. There is a significant amount of literature supporting the safety of vaccination during pregnancy. As other vaccines are newly introduced for pregnant women, routine systems for monitoring vaccine safety in pregnant women are needed. To facilitate meta-analyses and comparison across systems and studies, future research and surveillance initiatives should utilize the same criteria for defining adverse events following immunization among pregnant women. At least 2 areas require further exploration: 1) identification of pregnancy outcomes associated with concomitant and closely spaced vaccines; 2) evaluation of possible improvement in birth outcomes associated with maternal vaccination. Given the public health impact of maternal vaccination, the existing evidence supporting the safety of vaccination during pregnancy should be used to reassure pregnant women and their providers and improve vaccine uptake in pregnancy.